CXCL16/CXCR6 Axis Drives Microglia/Macrophages Phenotype in Physiological Conditions and Plays a Crucial Role in Glioma - Lepore, Francesca; D'Alessandro, Giuseppina; Antonangeli, Fabrizio; Santoro, Antonio; Esposito, Vincenzo; Limatola, Cristina; Trettel, Flavia (Frontiers in Immunology, 2018)
Microglia are patrolling cells that sense changes in brain microenvironment and respond acquiring distinct phenotypes that can be either beneficial or detrimental for brain homeostasis. Anti-inflammatory microglia release soluble factors that might promote brain repair; however, in glioma, anti-inflammatory microglia dampen immune response and promote a brain microenvironment that foster tumor growth and invasion. The chemokine CXCL16 is expressed in the brain, where is neuroprotective against brain ischemia, and it has been found to be over-expressed in glioblastoma (GBM). Considering that CXCL16 specific receptor CXCR6 is diffusely expressed in the brain including in microglia cells, we wanted to investigate the role of CXCL16 in the modulation of microglia cell activity and phenotype, and in the progression of glioma. Here we report that CXCL16 drives microglia polarization towards anti-inflammatory phenotype, also restraining microglia polarization towards an inflammatory phenotype upon LPS and IFNstimulation. In the context of glioma, we demonstrate that CXCL16 released by tumor cells is determinant in promoting glioma associated microglia/macrophages (GAMs) modulation towards an anti-inflammatory/pro-tumor phenotype, and that, cxcr6ko mice brain-transplanted with GL261 glioma survive longer compared to wild-type mice. We also describe that CXCL16/CXCR6 signaling acts directly on glioma cells, as well as human primary GBM cells, promoting tumor cell growth, migration and invasion. All together these data suggest that CXCL16 signaling could represent a good target to modulate microglia phenotype in order to restrain inflammation or to limit glioma progression.